Composite sulfide solid electrolyte and preparation method and application thereof
By setting oxide solid electrolyte layers on both sides of the sulfide solid electrolyte layer, the problems of sulfide electrolyte sensitivity to the environment and interface reaction are solved, the cycle stability and lithium puncture resistance of the battery are improved, and the battery performance is improved and reduce production costs.
Patent Information
- Application Number
- CN202411414484.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
Sulfide solid electrolyte is sensitive to the environment, easy to decompose, and an irreversible interface reaction occurs when in contact with high-voltage positive electrode material, resulting in a degradation of battery performance.
The oxide solid electrolyte layer is arranged on both sides of the sulfide solid electrolyte layer, including Li1.3Al0.3Ti1.7(PO4)3 and Li7La3Zr2O12, nanoparticles such as TiO2 or Al2O3, and composite sulfide electrolyte is formed through the coating process to improve the battery's Interface stability and environmental tolerance.
It significantly improves the cycle stability and lithium puncture resistance of the battery, extends the battery life, simplifies the preparation process, and reduces production costs.
Smart Images

Figure CN119297381A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a composite sulfide solid electrolyte and a preparation method and application thereof. Background Art
[0002] Sulfide solid electrolytes have attracted widespread attention in the field of all-solid-state lithium batteries in recent years. Due to their high lithium ion conductivity, low interfacial resistance and good formability at room temperature, they have become an important candidate material for the next generation of high-performance solid-state batteries. Although sulfide electrolytes have excellent ionic conductivity and mechanical properties, they are highly sensitive to the environment, especially to moisture and oxygen in the air. When exposed to air or moisture, sulfide electrolytes easily decompose to produce hydrogen sulfide (H2S) gas, causing material failure. Therefore, sulfide solid electrolytes have poor air stability and require strict environmental control during manufacturing and use. In addition, when sulfide electrolytes are in direct contact with high-voltage positive electrodes (such as oxide positive electrode materials such as NCM and NCA), irreversible interfacial reactions are prone to occur, forming byproducts that hinder lithium ion transmission. In order to overcome the limitations of sulfide solid electrolytes, researchers have proposed a strategy in recent years: coating a layer of nanoparticle mixed oxide solid electrolyte on the surface of sulfide solid electrolytes. This coating technology can significantly improve the interfacial stability, environmental tolerance and electrochemical performance of the battery. Summary of the invention
[0003] The main purpose of the present invention is to provide a composite sulfide solid electrolyte and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.
[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0005] The embodiment of the present invention provides a composite sulfide solid electrolyte, which comprises: a sulfide solid electrolyte layer and an oxide solid electrolyte layer arranged on both sides of the sulfide solid electrolyte layer, wherein the oxide solid electrolyte layer is respectively Li 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte layer and Li7La3Zr2O 12 Oxide solid electrolyte layer; wherein the oxide solid electrolyte layer includes nanoparticles and oxide solid electrolyte, the nanoparticles include TiO2 or Al2O3; the oxide solid electrolyte includes large-particle oxide solid electrolyte and small-particle oxide solid electrolyte.
[0006] The present invention also provides a method for preparing the composite sulfide solid electrolyte, which comprises:
[0007] The nanoparticles were mixed with Li 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte, Li7La3Zr2O 12 Oxide solid electrolyte mixed grinding to form Li 1.3 Al 0.3 Ti 1.7 (PO4)3 mixture and Li7La3Zr2O 12 Mixture;
[0008] And, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 mixture and Li7La3Zr2O 12 The mixed materials are coated on both sides of the sulfide solid electrolyte respectively, and then sintered at 400-700°C to obtain a composite sulfide solid electrolyte.
[0009] The embodiment of the present invention also provides the use of the aforementioned composite sulfide solid electrolyte in preparing a battery positive electrode sheet or a lithium ion battery.
[0010] The embodiment of the present invention also provides a battery positive electrode sheet, which includes: a positive electrode active material and a solid electrolyte; wherein the solid electrolyte includes the aforementioned composite sulfide solid electrolyte, and the Li 1.3 Al 0.3 Ti 1.7 The (PO4)3 oxide solid electrolyte layer is in contact with the positive electrode active material.
[0011] The embodiment of the present invention further provides a battery negative electrode sheet, which includes: a negative electrode material and a solid electrolyte; wherein the solid electrolyte includes the aforementioned composite sulfide solid electrolyte, and the Li7La3Zr2O in the composite sulfide solid electrolyte 12 The oxide solid electrolyte layer is in contact with the negative electrode material.
[0012] The present invention also provides a lithium-ion battery, which comprises: a positive electrode, a negative electrode and a solid electrolyte as an intermediate layer; wherein the solid electrolyte comprises the aforementioned composite sulfide solid electrolyte, and the Li 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte layer is in contact with the positive electrode, Li7La3Zr2O 12 The oxide solid electrolyte layer is in contact with the negative electrode.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) The present invention improves the cycle stability of the sulfide full battery by using an oxide solid electrolyte coating process, effectively solving the problem of poor compatibility between the sulfide solid electrolyte and the positive and negative electrodes, thereby increasing the service life of the battery;
[0015] (2) The nanoparticles in the present invention increase the rigidity and elastic modulus of the electrolyte and improve the lithium puncture resistance of the battery;
[0016] (3) The preparation process provided by the present invention is simple, low-cost, conducive to large-scale production, and has high practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 is a SEM image of the oxide solid electrolyte layer in Example 1 of the present invention;
[0019] Figure 2 is a cross-sectional view of the composite sulfide solid electrolyte in Example 1 of the present invention;
[0020] Figure 3 is a graph of ionic conductivity of the composite sulfide solid electrolyte and sulfide in Example 1 of the present invention;
[0021] Figure 4 It is a schematic cross-sectional view of a composite sulfide solid electrolyte in a typical embodiment of the present invention. DETAILED DESCRIPTION
[0022] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Specifically, as one aspect of the technical solution of the present invention, a composite sulfide solid electrolyte comprises: a sulfide solid electrolyte layer and an oxide solid electrolyte layer arranged on both sides of the sulfide solid electrolyte layer, wherein the oxide solid electrolyte layer is respectively Li 1.3 Al 0.3 Ti1.7 (PO4)3 oxide solid electrolyte layer and Li7La3Zr2O 12 Oxide solid electrolyte layer; wherein the oxide solid electrolyte layer includes nanoparticles and oxide solid electrolyte, the nanoparticles include TiO2 or Al2O3; the oxide solid electrolyte includes large-particle oxide solid electrolyte and small-particle oxide solid electrolyte.
[0024] The cross-sectional schematic diagram of the composite sulfide solid electrolyte in the present invention is as follows Figure 4 shown.
[0025] In the present invention, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 is used for contact with the positive electrode. It is usually used on the positive electrode side because of its good air stability and good conductivity at higher voltages; Li7La3Zr2O 12 Used to contact the negative electrode, it has good chemical stability and high lithium ion conductivity, especially compatible with metallic lithium, so it is usually used on the negative electrode side.
[0026] In some preferred embodiments, the thickness of the oxide solid electrolyte layer is a, the thickness of the sulfide solid electrolyte layer is b, and a=(1% to 50%)b, wherein the value range of b is 0.8-1.2min.
[0027] Furthermore, when the thickness a of the oxide solid electrolyte layer and the thickness b of the sulfide solid electrolyte layer satisfy the above formula, the oxide solid electrolyte layer does not affect the overall ionic conductivity and can protect the sulfide solid electrolyte.
[0028] In some preferred embodiments, the particle size D of the oxide solid electrolyte is 50 is c, the particle size D of the nanoparticles 50 It is d, and satisfies d=(1%~10%)c, where the value range of c is 0.1-100μm.
[0029] In some preferred embodiments, the mass of the nanoparticles in the oxide solid electrolyte layer is e, the mass of the oxide solid electrolyte is f, and the following relation is satisfied: e=(5% to 20%)f.
[0030] In some preferred embodiments, the oxide solid electrolyte includes 20-50 wt % of large-particle oxide solid electrolyte and 50-80 wt % of small-particle oxide solid electrolyte.
[0031] Furthermore, the particle size of the large-particle oxide solid electrolyte is 1-100 μm.
[0032] Furthermore, the particle size of the small-particle oxide solid electrolyte is less than 1 μm.
[0033] In some preferred embodiments, the sulfide solid electrolyte in the sulfide solid electrolyte layer includes LPSCl, wherein LPSCl is Li 5.5 PS 4.5 Cl 1.5 .
[0034] In some preferred embodiments, the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (denoted as: LATP) and / or Li7La3Zr2O 12 (denoted as: LLZO), and is not limited thereto.
[0035] In some preferred embodiments, the room temperature ionic conductivity of the composite sulfide solid electrolyte is 1.0E-4 to 1.0E-2 S / cm.
[0036] In the present invention, nano-TiO2 or Al2O3 and various oxide solid electrolytes Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) or Li7La3Zr2O 12 (LLZO) mixture, denoted as LATP*xTiO2 or LATP*xAl2O3, is coated on the surface of the sulfide solid electrolyte layer LPSCl connected to the positive electrode; LLZO*yTiO2 or LLZO*yAl2O3 is coated on the surface of the sulfide solid electrolyte LPSCl connected to the negative electrode.
[0037] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned composite sulfide solid electrolyte, which comprises:
[0038] The nanoparticles were mixed with Li 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte, Li7La3Zr2O 12 Oxide solid electrolyte mixed grinding to form Li 1.3 Al 0.3 Ti 1.7 (PO4)3 mixture and Li7La3Zr2O 12 Mixture;
[0039] And, Li 1.3 Al 0.3 Ti 1.7(PO4)3 mixture and Li7La3Zr2O 12 The mixed materials are coated on both sides of the sulfide solid electrolyte respectively, and then sintered at 400-700°C to obtain a composite sulfide solid electrolyte.
[0040] In some more specific embodiments, the method for preparing the composite sulfide solid electrolyte comprises the following steps:
[0041] 1. Precursor preparation:
[0042] Preparation of oxide solid electrolyte: LLZO or LATP is prepared, and nanoparticles are dispersed in LLZO oxide solid electrolyte and LATP oxide solid electrolyte respectively, mixed and ground to form LLZO mixture and LATP mixture. The particle size of oxide solid electrolyte is controlled between 0.1-100μm to improve the mechanical properties of the interface and the ionic conductivity of the material.
[0043] 2. Coating steps:
[0044] The LLZO mixture and the LATP mixture are uniformly coated on both sides of the sulfide solid electrolyte.
[0045] 3. Sintering:
[0046] Sintering: The coating material usually needs to be sintered at a temperature between 400-700°C to ensure that the coating is dense, uniform, and has sufficient mechanical strength.
[0047] Another aspect of the embodiments of the present invention further provides the use of the aforementioned composite sulfide solid electrolyte in the preparation of a battery positive electrode sheet or a lithium-ion battery.
[0048] Another aspect of the embodiment of the present invention further provides a battery positive electrode sheet, which includes: a positive electrode active material and a solid electrolyte; wherein the solid electrolyte includes the aforementioned composite sulfide solid electrolyte, and the Li 1.3 Al 0.3 Ti 1.7 The (PO4)3 oxide solid electrolyte layer is in contact with the positive electrode active material.
[0049] Another aspect of the embodiment of the present invention further provides a battery negative electrode sheet, which includes: a negative electrode material and a solid electrolyte; wherein the solid electrolyte includes the aforementioned composite sulfide solid electrolyte, and the Li7La3Zr2O in the composite sulfide solid electrolyte 12 The oxide solid electrolyte layer is in contact with the negative electrode material.
[0050] Another aspect of the embodiment of the present invention further provides a lithium-ion battery, which includes: a positive electrode, a negative electrode and a solid electrolyte as an intermediate layer; wherein the solid electrolyte includes the aforementioned composite sulfide solid electrolyte, and the Li 1.3 AI 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte layer is in contact with the positive electrode, Li7La3Zr2O 12 The oxide solid electrolyte layer is in contact with the negative electrode.
[0051] Further, the negative electrode includes a lithium metal negative electrode, but is not limited thereto.
[0052] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments. This embodiment is implemented on the premise of the technical solution of the invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0053] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0054] Positive electrode example 1: LATP large particles 50μm and small particles 0.6μm + 5wt% TiO2, composite coating 100nm
[0055] Material: Li 5.5 PS 4.5 Cl 1.5 As sulfide electrolyte, LATP as oxide coating material, 5wt% TiO2 nanoparticles doping. 5.5 PS 4.5 Cl 1.5 Mass 150mg, thickness 1mm, oxide mass 60mg, coating thickness 0.5mm.
[0056] Process: TiO2 nanoparticles are mixed with LATP and coated on Li 5.5 PS 4.5 Cl 1.5 The electrolyte surface was dried and sintered at 500 °C for 1 hour. 5.5 PS 4.5 Cl 1.5 The mixture is mixed and then evenly added to the surface of the composite electrolyte, and a positive electrode sheet is prepared by pressing the sheet using a certain pressure.
[0057] Results: The coated samples showed higher interfacial stability, and in high-voltage cathodes (such as NCM811), the capacity retention rate exceeded 80% after 100 cycles, while the uncoated samples were only about 75%.
[0058] Positive electrode comparative example 1: uncoated sample
[0059] Material: Li 5.5 PS 4.5 Cl 1.5 Sulfide electrolyte, no oxide coating.
[0060] Results: When the uncoated sample was paired with the NCM811 cathode, the interfacial impedance increased significantly after 100 cycles and the cycle stability decreased significantly, ultimately resulting in a capacity retention rate of less than 80%.
[0061] Negative electrode example 2: LLZO + 5wt% Al2O3 composite coating
[0062] Material: Li 5.5 PS 4.5 Cl 1.5 Sulfide electrolyte, LLZO oxide coating material, 3wt% Al2O3 nanoparticle doping.
[0063] Process: Coat the LLZO and Al2O3 mixed solution on the surface of the sulfide electrolyte, dry it and sinter it at 400℃ for 2 hours. Cut the Li metal into 9mm diameter and place it under the electrolyte sheet. Use a certain pressure to shape it and then perform a cycle test under a certain pressure.
[0064] Results: The LLZO+Al2O3 coated samples showed better cycle life under lithium metal anode conditions, with a capacity retention of 80% after 100 cycles, while the comparative samples failed quickly.
[0065] Negative electrode comparative example 2: uncoated sample
[0066] Material: Li 5.5 PS 4.5 Cl 1.5 Sulfide electrolyte, no oxide coating.
[0067] Results: When the uncoated sample was paired with the NCM811 cathode, the interfacial impedance increased significantly after 100 cycles and the cycle stability decreased significantly, ultimately resulting in a capacity retention rate of less than 80%.
[0068] Example 1
[0069] Step 1: Li 5.5 PS 4.5 Cl 1.5The thickness of the sulfide electrolyte is 1mm, and the thickness of the oxide coating material LATP and LLZO as the positive and negative contact surfaces is 0.5mm, and 5wt% TiO2 nanoparticles are doped. Then sintering is performed at a temperature of 500℃ to ensure that the coating is dense, uniform, and has sufficient mechanical strength. 5.5 PS 4.5 Cl 1.5 The mass is 150 mg, the thickness is 1 mm, the mass of the oxide solid electrolyte layer is 60 mg, and the coating thickness is 0.5 mm. The SEM image of the oxide solid electrolyte layer in this embodiment is as follows Figure 1 As shown, the cross-section of the composite sulfide solid electrolyte is as follows Figure 2 As shown, the ionic conductivity of the composite sulfide solid electrolyte and the single sulfide in this embodiment is shown in FIG. Figure 3 shown.
[0070] Among them, oxide solid electrolytes LATP, LLZO, sulfide solid electrolytes LPSCl and nanoparticles need to meet the following requirements:
[0071] (1) The particle sizes of the oxide solid electrolytes LATP and LLZO are 50 μm for large particles and 1 μm for small particles;
[0072] (2) 30 wt% of the oxide solid electrolyte is a large-particle oxide solid electrolyte and 70 wt% of the small-particle oxide solid electrolyte is a small-particle oxide solid electrolyte.
[0073] (3) The particle size of the sulfide solid electrolyte LPSCl is 3 μm;
[0074] (4) Particle size D of nanoparticle additives 50 is 50 nm; and its weight percentage is 5% of the whole mixture (the sum of LATP and LLZO);
[0075] Step 2: Mix the composite solid electrolyte with the positive electrode materials LiTiO4, LFP, and NCM in a mass ratio of 1:1 and add them to the electrolyte sheet for further compaction.
[0076] Step 3: Place the negative electrode lithium into the mold to obtain a sulfide full battery. During this process, the battery's charge cutoff voltage is controlled to be 4.2V and the discharge cutoff voltage is controlled to be 2.75V.
[0077] Step 4: The prepared sulfide full battery was left at room temperature for 24 hours, and then the charge and discharge test was performed. During the test, the charge and discharge current was controlled to be 0.5C, and the charge and discharge voltage range was 2.75V-4.2V.
[0078] Example 2
[0079] The method is the same as that of Example 1, except that the thickness of the oxide solid electrolyte layer is 10 nm, the mass of the oxide solid electrolyte is 5 mg, and the mass of the nano-additive is 0.25 mg.
[0080] Example 3
[0081] The method is the same as in Example 1, except that the mass of the nano additive is adjusted to 12 mg.
[0082] Example 4
[0083] The method is the same as in Example 1, except that the particles of the nano additive are 500 nm.
[0084] Comparative Example 1
[0085] The method is the same as in Example 1, except that no nanoparticles are added.
[0086] Comparative Example 2
[0087] The method is the same as in Example 1, except that: the thickness of the oxide solid electrolyte layer is a, the thickness of the sulfide solid electrolyte layer is b, and a=0.5%b;
[0088] Comparative Example 3
[0089] The method is the same as in Example 1, except that: the thickness of the oxide solid electrolyte layer is a, the thickness of the sulfide solid electrolyte layer is b, and a=70%b;
[0090] Comparative Example 4
[0091] The method is the same as in Example 1, except that: only large particles of the oxide solid electrolyte are used;
[0092] Comparative Example 5
[0093] The method is the same as in Example 1, except that: the oxide solid electrolyte uses only small particles;
[0094] Comparative Example 6
[0095] The method is the same as in Example 1, except that: the particle size D of the oxide solid electrolyte is 50 is c, the particle size D of the nanoparticles 50 is d, d = 0.5% c;
[0096] Comparative Example 7
[0097] The method is the same as in Example 1, except that: the particle size D of the oxide solid electrolyte is 50 is c, the particle size D of the nanoparticles 50 is d, d = 20% c;
[0098] Comparative Example 8
[0099] The method is the same as in Example 1, except that: the mass e of the nano-additive is relative to the mass f of the oxide solid electrolyte, and the relationship is e=1%f;
[0100] Comparative Example 9
[0101] The method is the same as in Example 1, except that: the mass e of the nano-additive is relative to the mass f of the oxide solid electrolyte, and the relationship is e=50%f;
[0102] The process parameters and test performances used for positive electrode sheet example 1, positive electrode sheet comparative example 1, negative electrode sheet example 2, negative electrode sheet comparative example 2, embodiments 1-4, and comparative examples 1-10 are shown in Table 1.
[0103] Table 1
[0104]
[0105]
[0106] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0107] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A composite sulfide solid electrolyte, characterized in that: include: A sulfide solid electrolyte layer and an oxide solid electrolyte layer disposed on both sides of the sulfide solid electrolyte layer, wherein the oxide solid electrolyte layer is Li 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte layer and Li7La3Zr2O 12 Oxide solid electrolyte layer; wherein the oxide solid electrolyte layer includes nanoparticles and oxide solid electrolyte, the nanoparticles include TiO2 or Al2O3; the oxide solid electrolyte includes large-particle oxide solid electrolyte and small-particle oxide solid electrolyte.
2. The composite sulfide solid electrolyte according to claim 1, characterized in that: The thickness of the oxide solid electrolyte layer is a, the thickness of the sulfide solid electrolyte layer is b, and a=(1%-50%)b is satisfied, wherein the value range of b is 0.8-1.2 mm.
3. The composite sulfide solid electrolyte according to claim 1, characterized in that: The particle size D of the oxide solid electrolyte 50 is c, the particle size D of the nanoparticles 50 It is d, and satisfies d=(1%~10%)c, where the value range of c is 0.1-100μm.
4. The composite sulfide solid electrolyte according to claim 1, characterized in that: The mass of the nanoparticles in the oxide solid electrolyte layer is e, the mass of the oxide solid electrolyte is f, and the following is satisfied: e=(5% to 20%)f; And / or, the oxide solid electrolyte comprises 20-50wt% large-particle oxide solid electrolyte and 50-80wt% small-particle oxide solid electrolyte; preferably, the particle size of the large-particle oxide solid electrolyte is 1-100μm; preferably, the particle size of the small-particle oxide solid electrolyte is less than 1μm.
5. The composite sulfide solid electrolyte according to claim 1, characterized in that: The sulfide solid electrolyte in the sulfide solid electrolyte layer includes LPSCl; And / or, the room temperature ionic conductivity of the composite sulfide solid electrolyte is 1.0E-4 to 1.0E-2 S / cm.
6. The method for preparing the composite sulfide solid electrolyte according to any one of claims 1 to 5, characterized in that: include: The nanoparticles were mixed with Li 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte, Li7La3Zr2O 12 Oxide solid electrolyte mixed grinding to form Li 1.3 Al 0.3 Ti 1.7 (PO4)3 mixture and Li7La3Zr2O 12 Mixture; And, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 mixture and Li7La3Zr2O 12 The mixed materials are coated on both sides of the sulfide solid electrolyte layer respectively, and then sintered at 400-700°C to obtain a composite sulfide solid electrolyte.
7. Use of the composite sulfide solid electrolyte according to any one of claims 1 to 5 in preparing a positive electrode sheet, a negative electrode sheet or a lithium ion battery.
8. A positive electrode sheet for a battery, characterized in that: include: A positive electrode active material and a solid electrolyte; wherein the solid electrolyte comprises a composite sulfide solid electrolyte according to any one of claims 1 to 5, and Li in the composite sulfide solid electrolyte 1.3 Al 0.3 Ti 1.7 The (PO4)3 oxide solid electrolyte layer is in contact with the positive electrode active material.
9. A battery negative electrode sheet, characterized in that: include: Anode material and solid electrolyte; wherein the solid electrolyte comprises the composite sulfide solid electrolyte according to any one of claims 1 to 5, and the Li7La3Zr2O 12 The oxide solid electrolyte layer is in contact with the negative electrode material.
10. A lithium ion battery, characterized in that: include: A positive electrode, a negative electrode and a solid electrolyte as an intermediate layer; wherein the solid electrolyte comprises a composite sulfide solid electrolyte as described in any one of claims 1 to 5, and Li in the composite sulfide solid electrolyte 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte layer is in contact with the positive electrode, Li7La3Zr2O 12 The oxide solid electrolyte layer is in contact with the negative electrode.